1996
DOI: 10.3109/09637489609012576
|View full text |Cite
|
Sign up to set email alerts
|

Protein-energy malnutrition in low income elderly Nairobi women

Abstract: Nutritional data for two groups of low income elderly women (chi = 64, range 57-74 years) in Nairobi, Kenya were compared. Group I (n = 113), slum dwellers, had an income of < or = $20 Cd per month; Group II (n = 88), poor urban area inhabitants, had an income of < or = $170 Cd per month. Dietary intakes were assessed quantitatively by four 24-h dietary recalls; anthropometric and biochemical data were obtained. Twenty-one women (16% of Group I; 3% of Group II) were classified as having protein-energy malnutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…The pattern revealed is similar to patterns reported in other African countries (Ndaba & O'Keefe, 1985;Thoner, 1993;Aspray et al, 1994;Ethangatta et al, 1996;Pieterse, 1997) as well as in other developing countries such as India (Marlow et al, 1996;Manandhar et al, 1997b), Sarawak (Strickland & Ulijaszek, 1993) and China (Side et al, 1991). The Asians however, were slightly shorter than Malawians re¯ecting either genetic or urban±rural differences since most of the Asian studies were conducted in urban areas.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The pattern revealed is similar to patterns reported in other African countries (Ndaba & O'Keefe, 1985;Thoner, 1993;Aspray et al, 1994;Ethangatta et al, 1996;Pieterse, 1997) as well as in other developing countries such as India (Marlow et al, 1996;Manandhar et al, 1997b), Sarawak (Strickland & Ulijaszek, 1993) and China (Side et al, 1991). The Asians however, were slightly shorter than Malawians re¯ecting either genetic or urban±rural differences since most of the Asian studies were conducted in urban areas.…”
Section: Discussionsupporting
confidence: 72%
“…Malnutrition among older people has been reported in developed countries (Lipschitz, 1992;Stuckey et al, 1984;DHSS, 1979;DHSS, 1972) and to a limited extent, in developing countries (Marlow et al, 1996;Ethangatta et al, 1996;Thoner, 1993;Yassin & Terry, 1991;Ndaba & O'Keefe, 1985). In Africa, studies on the well being of older people are now emerging (Allain et al, 1997;Aspray et al, 1996;Angura & Anyuru, 1994;Coombes et al, 1994;Nmadu, 1994;Matuja et al, 1994;McLigeyo, 1993;Wilson et al, 1991;Olubuyide et al, 1991;Apt, 1990;Pappoe et al, 1990;Hampson, 1985;Waterston, 1982;Drury, 1972) but most lack crucial nutrition data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein was derived mainly from plants; animal protein and dairy intake were very low 10,13,38 . Among elderly women living in underserved areas of Nairobi, Kenya, a mean of only 6 g/d was reported for animal protein 17,45 . About a quarter (27%) of the elderly in Zimbabwe ate a protein‐containing meal less than once a week, and 17.6% of black South Africans had intakes that were less than 66% of Dietary Reference Intakes (DRI), the lower reference value for adequate intake 17,29,46 …”
mentioning
confidence: 99%
“…PEM was also observed in people who could not eat sufficient dairy products because of low income (or other reasons) (8). Animal experiments have shown that several foods and food components such as antioxidants improve or protect against hepatic steatosis induced by several triggers, alcohol (9), carbon tetrachloride (10) and streptozotocin diabetes (11).…”
mentioning
confidence: 99%